Surgical treatment of acute necroticohemorrhagic pancreatitis. - Cazabán, Luis A; Baldizán, Jorge W; Carriquiry, Luis A (Cirugía del Uruguay, 1977)
In a series of 24 patients suffering from this condition, death-rate amounted to 75 %- On the basis of evolution of lesions found, a change in therapy is suggestecÍ: complete treatment of biliary lesions, continuous postoperatory peritoneal lavage and feeding jejunostomy. Greater experience will make it possible to establish_ definite value of this surgical treatment, befare the 8th day of evolution.